Group music therapy impacts mood states of adolescents in a psychiatric hospital setting. (July 2016) - Shuman, Jonah; Kennedy, Heather; DeWitt, Peter; Edelblute, Anthony; Wamboldt, Marianne Z.
Highlights: Group music therapy significantly impacts moods of adolescents. Music therapy integrates well into pediatric psychiatry units. Music therapy impacts moods regardless of gender, ethnicity, or diagnosis. Abstract: Although Music Therapy, an allied health discipline, is often included in standard care for the treatment of children with mental health disorders, there is a lack of empirical evidence to support its contribution for the care of children and adolescents in mental health services. The goal of this retrospective research is to examine whether group music therapy affects mood states of adolescent inpatients in a psychiatric hospital service based within a large children's hospital. A secondary aim was to understand if specific patient demographic predictors influenced the mood outcome. Participants included 352 predominately white, non-Hispanic patients (12–21 years old, with a mean age of 15.13 ± 1.88 years) who completed 596 mood measures between August 2010 and March 2013. Participants completed the Fast Assessment of Children's Emotions (FACE) before and after a group music therapy session. Based on a binary outcome model of change or no change, the probability of a change in total mood score was high (probability of change 0.82 [95%CI 0.79, 0.85]). There were no significant associations between age, gender, or other specific demographics that were tested, nor changes in individual or total mood scores within this sample. This preliminary research documents the immediate impact of group music therapy sessions on mood of adolescent patients in this setting diagnosed with a range of psychiatric disorders.